Alternative Routes to Oral Opioid Administration in Palliative Care: A Review and Clinical Summary. Issue 7 (4th July 2014) - Kestenbaum, Matthew G.; Vilches, Agustin O.; Messersmith, Stephanie; Connor, Stephen R.; Fine, Perry G.; Murphy, Brian; Davis, Malene; Muir, J. Cameron
Abstract Objective A major goal of palliative care is to provide comfort, and pain is one of the most common causes of treatable suffering in patients with advanced disease. Opioids are indispensable for pain management in palliative care and can usually be provided by the oral route, which is safe, effective, and of lowest cost in most cases. As patients near the end of life, however, the need for alternate routes of medication increases with up to 70% of patients requiring a nonoral route for opioid administration. In order to optimize patient care, it is imperative that clinicians understand existing available options of opioid administration and their respective advantages and disadvantages. Methods We performed a literature review to describe the most commonly used and available routes that can substitute for oral opioid therapy and to provide a summary of factors affecting choice of opioid for use in palliative care in terms of benefits, indications, cautions, and general considerations. Results Clinical circumstances will largely dictate appropriateness of the route selected. When the oral route is unavailable, subcutaneous, intravenous, and enteral routes are preferred in the palliative care population. The evidence supporting sublingual, buccal, rectal, and transdermal gel routes is mixed. Conclusions This review is not designed to be a critical appraisal of the quality of current evidence; rather, it is a summation of that evidence and of current clinical practices regarding alternate routes of opioid administration. In doing so, the overarching goal of this review is to support more informed clinical decision making.